Analisis Preferensi Konsumen Kedai Ruang Coffe Di Mogolaing Kecamatan Kotamobagu Barat Kota Kotamobagu Sulawesi Utara - Gobel, Viva Crisdaya; Maweikere, Audrey Julia Maria; Rengkung, Leonardus Ricky (Sam Ratulangi University, 2024)
The study aims to analyze consumer preferences for Kedai Ruang Coffee located in Mogolaing, Kotamobagu Barat District, Kotamobagu City, North Sulawesi. This research was conducted from July to December 2023 at the Kedai Ruang Coffee location in Mogolaing, Kotamobagu Barat District, Kotamobagu City. The study employed data collection methods including the distribution of questionnaires, interviews, and literature review. The sampling technique used was non-probability sampling, specifically accidental sampling, with a total of 40 respondents, averaging 10 respondents per day. The data were analyzed qualitatively and described descriptively, while quantitative analysis was performed using Likert scales to determine consumer preferences through Important Performance Analysis. Data processing was done using Microsoft Excel 2007 software. The results indicate that consumer preferences for Kedai Ruang Coffee are categorized into 13 attributes divided into 4 quadrants. Attributes in quadrant I which are the top priority, namely the attribute of hospitality to customers. Attributes in quadrant II that are included in maintaining achievement, namely politeness to customers, ease of communication, cleanliness and tidiness of the place, attractive place decoration and available equipment facilities. Quadrant III attributes that include low priority, namely timeliness in serving consumers, employee skills and abilities, speed of the serving process, employee alertness when customers visit, readiness and willingness to serve customers and ease in responding to requests. Attributes in quadrant IV that are considered excessive, namely the neatness attribute of the waiter's appearance.